Environmental Heritage, History and Biodiversity - Marcos Gerhardt; Eunice Sueli Nodari (Fronteiras: Journal of Social, Technological and Environmental Science, 2016)
This article analyzes the concept of environmental heritage and its significance for contemporary societies from the concepts of historical, cultural and natural heritage. Thus the duality between nature and culture is discussed by environmental history, addressing, among other topics, the domestication of plants and animals as a result of the complex interaction between human societies and nature. Analyses are done through the interpretation of testimonies published by travelers and chroniclers of the nineteenth and twentieth centuries. Moreover, official documents are used, both national and international, to argue that conservation of biodiversity is one of the main elements of the environmental heritage.